Metacaspases: Potential Drug Target Against Protozoan Parasites - Vandana; Vandana; Rajnikant Dixit; Rajnarayan Tiwari; Anju Katyal; Kailash C. Pandey; Kailash C. Pandey (Frontiers Media S.A., 2019)
Among the numerous strategies/targets for controlling infectious diseases, parasites-derived proteases receive prime attention due to their essential contribution to parasite growth and development. Parasites produce a broad array of proteases, which are required for parasite entry/invasion, modification/degradation of host proteins for their nourishment, and activation of inflammation that ensures their survival to maintain infection. Presently, extensive research is focused on unique proteases termed as "metacaspases" (MCAs) in relation to their versatile functions in plants and non-metazoans. Such unique MCAs proteases could be considered as a potential drug target against parasites due to their absence in the human host. MCAs are cysteine proteases, having Cys-His catalytic dyad present in fungi, protozoa, and plants. Studies so far indicated that MCAs are broadly associated with apoptosis-like cell death, growth, and stress regulation in different protozoa. The present review comprises the important research outcomes from our group and published literature, showing the variable properties and function of MCAs for therapeutic purpose against infectious diseases.